Formation of heterobinuclear Pt-Au complexes by chelate ring-opening of cis-[Pt(κ2-C6R4PPh2)2] (R = H, F) - Mirzadeh, Nedaossadat; Bennett, M. A.; Waechtler, E.; Zhechkov, L.; Heine, Thomas; Bhargava, S. K. (Journal of Organometallic Chemistry, 2015)
Mixed metal complexes of the type [Pt(κ2-2-C6R4PPh2) (PPh3) (μ-2-C6R4PPh2)AuCl] (R = H, F) can be prepared by treatment of cis-[Pt(κ2-C6R4PPh2)2] with [AuCl(PPh3)]. Under similar reaction conditions, the trans isomer of [Pt(κ2-C6F4PPh2)2] is unreactive. Computational studies have been performed to provide insights into the reasons for this difference in reactivity. Density Functional Theory (DFT) calculations show that formation of an AuCl adduct of [Pt(κ2-2-C6R4PPh2)2] is favoured over nucleophilic addition of PPh3 to Pt as the initial step of the reaction, and reveal the required energy of the cis and trans isomers of the bis-chelate [Pt(κ2-2-C6R4PPh2)2] in forming the mixed metal Pt-Au compounds. NBO analysis sheds more light on the bonding orbitals of the cis and trans isomers, suggesting that the Pt-P bonds in the cis isomer are more labile.
CRIS-Team Scopus Importer:2023-03-20
Keywords: Gold; Mixed metal complexes; Platinum; Ring opening